Prevalence, risk factors, and vaccine effectiveness of COVID-19 infection in thai children, adolescents, and young adults in the omicron era - Chaiyakulsil, Chanapai; Sritipsukho, Paskorn; Satdhabudha, Araya; Bunjoungmanee, Pornumpa; Tangsathapornpong, Auchara; Sinlapamongkolkul, Phakatip; Sritipsukho, Naiyana (Frontiers in Pediatrics, 2023)
Background and objectives: The study of prevalence, risk factors, and vaccine effectiveness (VE) in children, adolescents, and young adults during the Omicron era has been limited, making this the objectives of the study. Methods: A prospective, test-negative case-control study was conducted on patients aged 0 – 24 years old classified as patients under investigation (PUI) from January to May 2022. PUI with positive RT-PCR within 14 days were classified as cases, whilst PUI with negative RT-PCR in 14 days were controls. Univariate and multivariate analyses determined risk factors; VE was calculated using (1-adjusted odds ratio (OR)) x 100. Results: The final analyses included 3,490 patients with a PUI infection rate of 45.6%. Heterologous vaccination regimens, including inactivated vaccines, viral vectors, and mRNA were utilized during the study period. A total of 2,563 patients (73.5%) had received at least 2 vaccine doses, regardless of regimen. Male gender and household infections were independent risk factors for the development of infection, with an adjusted OR of 1.55 and 1.45, respectively. Underlying comorbidities and obesity were not significantly associated with the development of infection. Patients with underlying comorbidities were more likely to have at least moderate severity of infection with the adjusted OR of 3.07. Age older than 11 years was associated with lower infection risk and development of at least moderate infection with adjusted OR of 0.4 and 0.34, respectively. Vaccinated participants also had a lower risk of developing at least moderate infection: adjusted OR of 0.40. The adjusted VE of any vaccination regimen for infection prevention for one, two, three, or more than four doses was 21.8%, 30.6%, 53.5%, and 81.2%, respectively. The adjusted VE of any vaccination regimen for prevention of at least moderate severity of the disease for one, two, three, or more than four doses was 5.7%, 24.3% 62.9%, and 90.6%, respectively Conclusion: Disease prevalence among PUI was substantially high during the Omicron wave. A two-dose vaccination regimen does not appear sufficient to ensure protection against infection. Keywords: COVID-19, Omicron, children, vaccine, vaccine effectiveness, adolescents, risk factors